Tanggung Jawab Notaris Untuk Melaporkan Dugaan Terjadinya Tindak Pidana Pencucian Uang - Adryani, Nadhilla Prijanka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The wheel of development has been fastly rolling up, more and more knowledge and technologies has been found in order to make human life easier. However, it turns out that this development does not always seem to be used for the good of mandkind, sometimes it missly used in deceiving or conducting crime act. One of their attempts to cover the crime act is by involving the Notary as public officials. The involvement of Notary may deceive the criminal trail such as the corruption money which deceives by conducting a money laundering, either by purchasing assets or establishing a legal entity. Therefore, this article discusses the authority of a Notary who has the potential to be involved in money laundering act and how far the Notary’s liability on reporting the money laundering allegation. In an effort to find the answer to the problem, this article uses normative legal research method and the materials are use primary and secondary legal materials.This article will also discuss what services a Notary provides and which are then linked to scheme of criminal acts of corruption and money laundering, so that it can be seen to what extent a Notary can be involved in fulfilling corruption and money laundering offenses. This Article will also discussed regarding the principle of confidentiality inherent in the position of a Notary. To explain this, this article uses a normative juridical method by using primary legal materials and secondary legal materials.